Enhancing Vocabulary Learning of Young Learners through Collaborative Strategies in English Classroom - Amelia Nurjihaan; Ummi Nur Laila Sulistyani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
The language development of young learners depends on their acquisition of fundamental English vocabulary. However, a lot of Indonesian elementary school students still have problems learning new words, especially those who live in rural regions. The purpose of this study was to investigate how well collaborative learning enhances young learners' vocabulary in English. Students in the second grade at SD Negeri 2 Pogung were included in a mixed methods study. While qualitative data came from student interviews and classroom observations, quantitative data was gathered using a pre-test and post-test design and examined using descriptive statistics and a paired samples t-test. The results showed that students' vocabulary achievement had significantly improved, with the mean score rising from 49.4 in the pre-test to 76.6 in the post-test. Additionally, the improvement was statistically significant (p <.001) according to the paired samples t-test. In addition to the quantitative improvements, qualitative findings revealed that students thought peer interaction and group activities were beneficial for learning, remembering, and using new vocabulary. The findings indicate that collaborative learning could serve as a useful educational strategy for improving vocabulary growth and student engagement for young learners, especially in elementary school settings that lack access to technology.